Tusaayaksat Building in Inuvik, NWT ... - Digital Library North; Stobbs, Robyn (University of Alberta Library, 2014)
The Tusaayaksat Building in Inuvik, NWT houses the Inuvilauit Cultural Resource Centre and the Inuvialuit Communications Society. ...